Math Gamification and ICT for University Learning: Systematic Review Article - Velásquez Lecca, Susana Mercedes (2023)
The integration of math gamification and Information and Communication Technologies (ICT) in learning has been a subject of growing interest. This approach seeks to improve student motivation and performance by transforming mathematics teaching into a more interactive and hands-on experience in university education. In this research the PRISMA method was used, 80,000 academic papers were systematically reviewed on ICT-supported math gamification in education whereof 79,994 academic papers corresponding to other fields were excluded, selecting and using at the end 55 articles to conduct this research. Studies were identified that explored the effectiveness of this combination at different educational levels, with a particular emphasis on higher education. The results highlight a significant increase in student engagement and motivation, as well as improvement in knowledge retention as shown in the figures and tables of this research. Instant ICT feedback and the application of digital educational games contributed to have a more active learning adapted to individual needs. Although the results are encouraging, challenges remain, such as the need for personalization and equity in ICT access. Continued research seeks to perfect these strategies maximizing the benefits of gamification and ICT, highlighting the importance of adapting to the diversity of learning styles in mathematics education.